Infrared micro-thermography of high-power AlInGaN LEDs using high emissivity (black) in IR and transparent in the visible spectral region coating. Issue 2 (3rd April 2019) - Aladov, A.; Chernyakov, A.; Zakgeim, A.
ABSTRACT: For modern high-power LEDs, self-heating becomes a critical factor determining their functional characteristics and lifetime. For large-area LEDs with a complex structure, it is important to know not only the thermal resistance but also the detailed temperature distribution (temperature map) over the active area. We report a technique which can simplify and improve the Infrared (IR) micro-thermography of light-emitting diodes (LEDs) by the use of a special thin-film coating which combines strong absorption in the wavelength range of sensitivity of IR microscope (2.5–3 μm) and transparency in the visible region of the own LED radiation. As known, conventional IR temperature measurements, made on the LEDs, lead to significant difficulties and errors as a consequence of the optical transparency of substrate/heterostructure layers and a low emissivity of metallised contacts. The proposed method allows avoiding the time-consuming procedure of emissivity calibration for different materials forming LEDs while increasing the measurement accuracy.